Settings of a novel electrosurgical generator to enable efficient and safe submucosal endoscopic procedures - Jawaid, Salmaan; Keihanian, Tara; Khalaf, Mai; Riojas-Barrett, Margarita; Abdeljaber, Wesam; Mercado, Michael; Zabad, Noor; Othman, Mohamed O. (Endoscopy International Open, 2023)
Background and study aims A novel electrosurgical generator unit (ESU), ConMed Beamer, was recently introduced to facilitate endoscopic submucosal dissection (ESD) by employing Automatic Cutting Effect (ACE) technology. Its use in submucosal endoscopy has yet to be investigated. The aim of this study was to evaluate the feasibility and safety of performing ESD and peroral endoscopic myotomy (POEM) using novel settings generated with ConMed Beamer ESU.Patients and methods This was a single-center prospective study of 59 consecutive patients undergoing ESD/POEM at a tertiary referral center. ESU settings were initially generated by testing in live animal models prior to first in-human study. The primary outcome was technical success. Secondary outcomes were procedure times, rate of en bloc/R0 resection, and rate of adverse events (AEs).Results A total of 44 patients (50 polyps) and 15 patients underwent ESD and POEM, respectively. En bloc resection, R0 resection, and curative resection rates were 90%, 77.1%, and 70.8%, respectively. Mean maximal length of the lesion was 3.07 cm ± 1.43 with an average dissection speed of 14.2 cm2/hr ± 11.1. Technical success was achieved in 100% of POEM patients. Mean time (minutes) to complete the POEM procedure was 50.1 min ± 12.4. Two major AEs occurred among all patients (3.4%). All intraprocedural bleeding events were controlled using the ConMed Beamer ESU.Conclusions ConMed Beamer ESU settings generated from this study were proven safe and effective in a prospective cohort of patients who underwent submucosal endoscopic procedures. This novel ESU can be added to the armamentarium of ESD capable generators.